Susanna Wesley - Ludwig, Charles; Nang ChanYeema (Milford, MI USA Mott Media, Inc., 1984)
A biography of the woman who married the well known preacher, Samuel Wesley, and was the mother of John, founder of Methodism, and Charles, famous for more than 6,000 hymns he wrote during his lifetime.
Keywords: Biography